This is a system of equations. First, you set everything in terms of y. Take the first equation and move set everything equal to y y=0+2x Since it’s 0, you don’t need to put it, so y=2x works. Then, you plug y=2x into the bottom equation, for the y. -7x +3(2x)=2. You do this because now you have the same variable for both and it can be solved easily. Then you can simplify. -7x+3x = 2 Then combine like terms. -4x = 2 Divide by -4 on each side. x = -1/2 So, now that you have x, you can plug in your x-value back into the top equation. -2(-1/2) + y = 0 Combine like terms 1+y=0 Get y by itself y=-1 There you have it! You can check by plugging in both values to any of the equations. We will use the top one here. -2(-1/2) + (-1) =0 +1 + -1 = 0 It works! So, X= -1/2 Y= -1 Please rate me Brainliest answer :)